2022
DOI: 10.1101/2022.09.07.22279497
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-world Effectiveness of Sotrovimab for the Early Treatment of COVID-19 During SARS-CoV-2 Delta and Omicron Waves in the United States

Abstract: Background Sotrovimab, a recombinant human monoclonal antibody (mAb) against SARS-CoV-2 had US FDA Emergency Use Authorization (EUA) for the treatment of high-risk outpatients with mild-to-moderate COVID-19 from May 26, 2021, to April 5, 2022. The study objective was to evaluate the real-world effectiveness of sotrovimab in reducing the risk of 30-day all-cause hospitalization and/or mortality during the time period when the prevalence of circulating SARS-CoV-2 variants was changing between Delta and Omicron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…32 Similarly, in an observational study in the US, treatment with sotrovimab was associated with a reduced risk of all-cause hospitalisation and mortality during the predominance of early Omicron variants. 33 This study has several limitations that should be considered. Firstly, the study presents descriptive analyses with no adjustments for differences in patient characteristics between cohorts, meaning that any potential associations may be subject to bias and confounding.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…32 Similarly, in an observational study in the US, treatment with sotrovimab was associated with a reduced risk of all-cause hospitalisation and mortality during the predominance of early Omicron variants. 33 This study has several limitations that should be considered. Firstly, the study presents descriptive analyses with no adjustments for differences in patient characteristics between cohorts, meaning that any potential associations may be subject to bias and confounding.…”
Section: Discussionmentioning
confidence: 95%
“…32 Similarly, in an observational study in the US, treatment with sotrovimab was associated with a reduced risk of all-cause hospitalisation and mortality during the predominance of early Omicron variants. 33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggarwal and colleagues examined effectiveness of sotrovimab among high-risk outpatients diagnosed with COVID-19 in Colorado during October 1, 2021 -December 11, 2021 when Delta was the predominant circulating variant and found a 63% lower odds of 28-day all-cause hospitalization and 89% lower odds of 28day all-cause mortality [7] Insurance Claims database found that patients receiving sotrovimab had a 55% lower risk of 30-day hospitalization or mortality (RR 0.45, 95% CI, 0.41 -0.49) and an 85% lower risk of 30-day mortality (RR 0.15, 95% CI, 0.08 -0.29) [18]. Like Aggarwal et al, Cheng et al found reduced, non-significant sotrovimab effectiveness during BA.2 predominance -RR 0.32, 95% CI, 0.04 -2.38 -in April 2022, with 68 doses of sotrovimab dispensed in an eligible population over 117 thousand.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in hospitalisations and deaths found in this study are broadly consistent with published preomicron randomised controlled trials for sotrovimab, 2 molnupiravir, 3 and nirmatrelvirritonavir, 4 despite our study being carried out when omicron was the predominant variant in Wales. Similar results were observed in real-world studies of nirmatrelvir-ritonavir 22 where a significant decrease in the rate of severe COVID-19 or death was observed with an adjusted HR of 0.54 (95%CI: 0.39-0.75) when omicron was the predominant variant, a preprint study of sotrovimab with a 55% relative risk (RR) reduction of hospitalisation (RR: 0.45, 95%CI: 0.41-0.49) before 23 and a study of sotrovimab with a 72% reduction in risk of hospitalisation (OR: 0.28, 95%CI: 0.11-0.71) after the emergence of omicron variants. 24 Our results contrast to those of the recently published 25,000 participant, prospective, openlabel, UK-wide, PANORAMIC trial, which found only a 1% risk of all-cause hospitalisation and that molnupiravir did not reduce the frequency of COVID-19-associated hospitalisations or death among adults over 50 years of age or over 18 with other risk factors, in the community.…”
Section: Findings In Contextmentioning
confidence: 91%